Application of Manure on Alluvial Soil to The Changes of Soil Chemical Properties - Andrayani, Ketti; Sangkala, Sangkala; Susilawati, Susilawati (Bionature, 2024)
The objective of the study is to test the chemical content of alluvial soil with the application of manure. Alluvial soil has poor physical and chemical soil properties, including low pH, nutrients, C-organic soil cation exchange capacity and a low C/N ratio. Therefore, it requires action to improve the planting by adding manure ameliorant. This research was carried out from February 5th, 2023, to April 5th, 2023 in Sambas Regency, Sambas District. This research uses a descriptive analysis model by comparing laboratory analyses using samples before and after the incubation process for 30 days. The treatments referred to in this research are: chicken manure, cow manure and goat manure. The dose of alluvial soil and manure used is 1:1. The parameters used in the research include soil pH, soil CEC, organic carbon (C), C/N ratio, elements nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg). The results of the research showed that there were changes in the chemical properties of the soil after being treated using chicken manure, cow manure and goat manure when compared to the untreated soil. The use of chicken manure on alluvial soil has a more beneficial effect on changes in soil pH values, soil CEC, C-organics, C/N ratio, N, P, K, Ca, and Mg elements when compared with the use of cow manure.